2G/3G connect: An educational software for teaching 2G/3G mobile communications to engineering students. Issue 1 (10th October 2012) - Sánchez‐García, J. Eulogio; Portilla‐Figueras, J. Antonio; Salcedo‐Sanz, Sancho; Jiménez‐Fernández, S.
Abstract Mobile communications have become one of the key points in the development of Information Society. Therefore the market demands to qualify engineers with a good formation on this topic, and more specifically related with good knowledge about the design and deployment of mobile and wireless networks and services of different technologies. For this reason most of the graduate and post‐graduate programs in Electrical and Electronic engineering studies consider at least one specific subject focused on mobile communications. However, the large number of concepts and the different existing technologies could make this subject very difficult for the student. This article presents a software tool for the design of second and third generation radio access networks, which makes easier the understanding and application of theoretical concepts, giving the student a more practical and realistic view of the subject. Furthermore as this tool has been applied for the regulation on mobile communications in different countries, the students can get some practical knowledge about the work in mobile communications in real world applications. © 2012 Wiley Periodicals, Inc. Comput Appl Eng Educ 23:1–12, 2015; View this article online at wileyonlinelibrary.com/journal/cae; DOI 10.1002/cae.21570